Proceedings of the Third International Conference on Sustainable Innovation 2019 – Health Science and Nursing (IcoSIHSN 2019) 2019
DOI: 10.2991/icosihsn-19.2019.28
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Gestational and Maternal Age with Pathological Neonatal Jaundice

Abstract: Pathologic jaundice is one of the causes of neonatal death, among the risk factor is pre-term pregnancy that causes prematurity. It affects the growth of the fetus due to the immaturity of the reproductive organs. The main objective of this study is to analyze the correlation between gestational and maternal age with pathologic neonatal jaundice. The research used quantitative analytical method with cross sectional approach. The sample consisted of 297 babies chosen using systematic random sampling technique. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Whereas maternal age either <20 or >35 years were at risk of developing pathological jaundice in newborns. 16 In our study, we found jaundice both in 21-30 years and 31-40 years group.…”
Section: Resultssupporting
confidence: 54%
“…Whereas maternal age either <20 or >35 years were at risk of developing pathological jaundice in newborns. 16 In our study, we found jaundice both in 21-30 years and 31-40 years group.…”
Section: Resultssupporting
confidence: 54%
“…This yellow color appears because the baby's liver needs adaptation so that bilirubin in the blood can be removed within a few weeks after birth. If there is failure or delay, serum or plasma bilirubin in the blood will cause yellow staining of the sclera throughout the baby's body (Fetriyah et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…According to research (Fetriyah et al, 2019) newborns produce high bilirubin due to an increase in the number of hematocrit and volume of red blood cells per body weight, red blood cells of newborns and shorter life spans (70 to 90 days) usually 120 day. Although bilirubin production is increased in newborns, the process of conjugation and clearance of bilirubin can be slow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation